Potensi Antibakteri Ekstrak (Graptophyllum Pictum (L.) Griff) Pada Porphyromonas gingivalis - Albert; Ameliya Az-Zahra, Syifa (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: The most prevalent bacteria found in periodontitis are the Gram-negative anaerobic stem bacteria Porphyromonas gingivalis. Periodontitis can potentially affect tooth mobility and tooth loss. Plaque control can be achieved using mechanical tools such as toothbrushes and interdental cleaners, which are reinforced by the use of antibacterial remedies as a chemical approach. Purple leaves contain chemical compounds including alkaloids, flavonoids, tannins, tripenoids, saponins, and glycosides. Objective:  To determine the effectiveness of purple leaves as an antibacterial inhibitor against Porphyromonas gingivalis. Methods: The experimental laboratory study with microdilution method, the breeding of Porphyromonas gingivalis ATCC 33277. The test material is purple leaf extract in six, Concentrations: 100%, 50%, 25%, 12.5%, 6.25%, and 3.125%, as well as aquades (negative control) and chlorhexidine 0.2% (positive control). The antibacterial test was carried out by counting the total bacterial colonies obtained using the formula for the average number of bacterial colonies. Results: In testing purple leaf extract against Porphyromonas gingivalis, the minimum inhibitory concentration (MIC) was obtained at a concentration of 3.125% and the minimum bactericidal concentration (MBC) was obtained at a concentration of 50%. Conclusion: Purple leaf extract is effective as an antibacterial against Porphyromonas gingivalis, starting at 50% and 100% concentrations.